Searching for leadership : secretaries to cabinet in Canada - Dutil, Patrice A., 1960- (Institute of Public Administration of Canada series in public management and governance., 2008)
"Although the subject of leadership is widely studied and debated, it has never attracted much attention in relation to the public sector. Searching for Leadership is the first book to examine the evolving role of the highest-ranking public servant both in Ottawa and in Canada's provinces and territories, namely, the secretary to cabinet or the clerk of the Executive Council." "An important contribution to our understanding of Canadian governance and public management, Searching for Leadership is essential reading for scholars and students in political science, history, and public administration and management, as well as for public servants."--Jacket